Air stripping of ammonia from wastewater - Bakti, Nordin Bin Abdul Kadir; Chongrak Polprasert; Nguyen, Cong Thanh; Samorn Muttamara; Malaysian Government (Bangkok : Asian Institute of Technology, 1980)
A mathematical model for the simulation of ammonia striping in crosscurrent spray system was presented. The use of the model for the design of the system was illustrated using the empirical relationships obtained in the laboratory. Experimental investigation revealed that the efficiency of the system increases with an increase in the initial ammonia concentration. Although the percent removal increases with the gas-to-liquid ratio, the unit efficiency based on unit air flow and initial ammonia concentration decreases with increasing gas-to-liquid ratio. The theoretical height of a transfer unit for ammonia (H0G)' which is the ratio of the gas rate to the volumetric overall gas-phase mass transfer coefficient was found to vary proportionally with gas-to-liquid ratio (G/L) in the ammonia concentration range between 140 mg/l and 225 mg/1, according to the following equation: in HOG= -0.3480 + 0.94 in(G/L) However, HOG was observed to be also influenced by the initial ammonia (Cf) at concentrations below 140 mg/l, according to the following equation: ln HOG = 6.2085 - 0.9525 ln Cf
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1980
Keywords: Sewage -- Purification -- Nitrogen removal